Ethics in Design and Implementation of Technologies for Workplace Health Promotion: A Call for Discussion - Roossien, Charlotte Christina; de Jong, Marlon; Bonvanie, Anne Maria; Maeckelberghe, Els Lisette Maria (Frontiers in Digital Health, 2021)
Aim This study aims to initiate discussion on ethical issues surrounding the development and implementation of technologies for workplace health promotion. We believe this is a neglected topic and such a complex field of study that we cannot come up with solutions easily or quickly. Therefore, this study is the starting point of a discussion about the ethics of and the need for policies around technologies for workplace health promotion. Method Based on a literature review, the present study outlines current knowledge on ethical issues in research, development and implementation of technologies in the workplace. Specifically, the focus is on two ethical issues that play an important role in the worker-employer relation: privacy and autonomy. Application Two cases indicative for a multidisciplinary project aimed at developing and evaluating sensor and intervention technologies that contribute to keeping workers healthy and effectively employable, are explored. A context-specific approach of ethics is used to investigate the ethical issues during the development and implementation of sensor and intervention technologies. It is a holistic approach towards the diverse field of participants and stakeholders, and the diversity in perceptions of relevant values, depending on their respective professional languages. Discussion The results show how protecting the privacy and autonomy of workers cannot be seen as stand-alone issues, but rather, there is an interplay between these values, the work context, and the responsibilities of workers and employers. Consequently, technologies in this research project are designed to improve worker conscientious autonomy, while concurrently creating balance between privacy and health, and assigning responsibilities to appropriate stakeholders. Conclusion Focusing on a contextual conceptualization of the ethical principles in the design and implementation of digital health technologies helps to avoid compartmentalization, out-of-context generalization, and neglect of identifying responsibilities. Although it is a long reiterative process in which all stakeholders need to be included in order to assess all ethical issues sufficiently, this process is crucial for achieving the intended goal of a technology. Having laid out the landscape and problems of ethics around technologies for workplace health promotion, we believe policies and standards, and a very overdue discussion on these, is needed.